(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
This research paper is a sincere attempt to gauge the discrimination prevalent in Indian society as described in Arundhati Roy’s novel The Ministry of Utmost Happiness which was published in 2017. Having different historical contexts, this novel is a reflection to various types of discriminations prevalent in the Indian society such as transgender discrimination that is based on gender identity, women discrimination that is based on male domination, dalit discrimination based on caste system, Muslim minority discrimination based on religious prejudice and national identity crisis based on multi-ethnic alienation that leads to the issue of identity crisis in the dislocated and disoriented people. The author has used a glut of historical event to represent the theme of identity crisis. The victims of discrimination suffer from personality disorder and feel alienated because they are incapable of synchronizing with the biased society.